Interindividual variability in cold-pressor pain sensitivity is not explained by peripheral vascular responding and generalizes to a C-nociceptor-specific pain phenotype - Martel, Richard; Papafragou, Georgios; Weigand, Sylvia; Rolke, Roman; Prawitt, Dirk; Birklein, Frank; Treede, Rolf-Detlef; Magerl, Walter (Pain, 2024)
Pain sensitivity of healthy subjects in the cold-pressor (CP) test was proposed to be dichotomously distributed and to represent a pain sensitivity trait. Still, it has not been systematically explored which factors influence this pain sensitivity readout. The aim of this study was to distinguish potential contributions of local tissue-related factors such as perfusion and thermoregulation or gain settings in nociceptive systems. Cold-pressor-sensitive and CP-insensitive students screened from a medical student laboratory course were recruited for a CP retest with additional cardiovascular and bilateral local vascular monitoring. In addition, comprehensive quantitative sensory testing according to Deutscher Forschungsverbund Neuropathischer Schmerz standards and a sustained pinch test were performed. Cold pressor was reproducible across sessions (Cohen kappa 0.61 ± 0.14, P < 0.005). At 30 seconds in ice water, CP-sensitive subjects exhibited not only more pain (78.6 ± 26.3 vs 29.5 ± 17.5, P < 0.0001) but also significantly stronger increases in mean arterial blood pressure (12.6 ± 9.3 vs 5.6 ± 8.1 mm Hg, P < 0.05) and heart rate (15.0 ± 8.2 vs 7.1 ± 6.2 bpm, P < 0.005), and lower baroreflex sensitivity, but not local or vasoconstrictor reflex-mediated microcirculatory responses. Cold-pressor-sensitive subjects exhibited significantly lower pain thresholds also for cold, heat, and blunt pressure, and enhanced pain summation, but no significant differences in Aδ-nociceptor-mediated punctate mechanical pain. In conclusion, differences in nociceptive signal processing drove systemic cardiovascular responses. Baroreceptor activation suppressed pain and cardiovascular responses more efficiently in CP-insensitive subjects. Cold-pressor sensitivity generalized to a pain trait of C-fiber-mediated nociceptive channels, which was independent of local thermal and vascular changes in the ice-water-exposed hand. Thus, the C-fiber pain trait reflects gain setting of the nociceptive system.